2019
DOI: 10.3762/bjnano.10.83
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Co/Nb pseudo spin valve for cryogenic memory

Abstract: We present a study of magnetic structures with controllable effective exchange energy for Josephson switches and memory applications. As a basis for a weak link we propose to use a periodic structure composed of ferromagnetic (F) layers spaced by thin superconductors (s). Our calculations based on the Usadel equations show that switching from parallel (P) to antiparallel (AP) alignment of neighboring F layers can lead to a significant enhancement of the critical current through the junction. To control the mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 40 publications
2
47
0
3
Order By: Relevance
“…where l is the length of the strip, W and d are the width and the thickness of the multilayer structure, respectively. It can be concluded that small changes in the temperature or in the applied magnetic field [ 9 ] can significantly change (from zero to relatively large values) the kinetic inductance of thin s-layers in the hybrid structures studied in this work.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…where l is the length of the strip, W and d are the width and the thickness of the multilayer structure, respectively. It can be concluded that small changes in the temperature or in the applied magnetic field [ 9 ] can significantly change (from zero to relatively large values) the kinetic inductance of thin s-layers in the hybrid structures studied in this work.…”
Section: Resultsmentioning
confidence: 93%
“…The next step was to experimentally verify the significant changes, predicted in the model, for the pair potential in thin s-layers of a [Co(1.5 nm)/Nb(8 nm)/Co(2.5 nm)/Nb(8 nm)] 3 AFM. For these superlattices, the possibility of switching between the P and AP cases, using a magnetic field with an intensity of ≈30 oersteds, has already been demonstrated [ 9 ]. The samples were prepared by using the magnetron sputtering system Leybold Heraeus Z-400 during a single deposition cycle without depressurization of the chamber.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Кроме того, в реальных материалах граница контактного слоя является достаточно протяженной и структурно неоднородной. Магнитные свойства конечного материала находятся в прямой зависимости от нанометровых магнитных кластеров и ферромагнитных доменов в зоне контакта, а также их взаимодействия между собой [21]. В связи с вышесказанным, актуальна задача детального исследования структуры контактного слоя слоистых материалов сверхпроводник-ферромагнетик и определения его пространственного профиля.…”
Section: ____________________________________________________________unclassified
“…В связи с вышесказанным, актуальна задача детального исследования структуры контактного слоя слоистых материалов сверхпроводник-ферромагнетик и определения его пространственного профиля. Для построения методологических основ и проведения теоретических исследований структуры многослойных спиновых систем в данной работе смоделирована наносистема с управляемой эффективной энергией обмена для устройств памяти и переключателей типа «спиновый вентиль» [22,23], представляющая собой многослойную структуру, состоящую из ферромагнитных нанопленок кобальта, которые разделены тонкими слоями сверхпроводника ниобия.…”
Section: ____________________________________________________________unclassified